The Williams Advanced Pinball Programming Logic Executive Operating System - Coriale, Maura (IEEE potentials, 2022)
Pinball has its roots in tabletop games from the late 1800s and early 1900s, although the 1930s marked the true start of pinball as we know it today. Early pinball was an electromechanical game, with points tallied by hand or through the movements of gears. For a while, it looked pretty far from what one would expect based on present-day pinball machines, which are known for their spring-loaded plungers, pair of flippers, bumpers, and drop targets. It was not until 1947 that the first pinball machine with flippers debuted (DeLeon, 2012) and set the precedent for decades to follow.